Pneumatocele in a Ugandan female with SARS‐CoV2 infection: A case report - Sanjanaa Srikant (Clinical Case Reports, 2022)
Abstract Pneumatocele may complicate the course of SARS‐CoV2 infection. Our article exhibits the value of early radiological imaging for the timely diagnosis and management of COVID‐19 and its complications. Conservative management is the mainstay of the treatment of pneumatoceles; however, prompt surgical intervention is imperative for complicated pneumatoceles.